Auswanderungsagenturen und Auswanderungsvereine im 19. und 20. Jahrhundert - Bretting, Agnes 1947- (Von Deutschland nach Amerika;, 1991)
Places special emphasis on the so-called emigration agencies, recruiters and emigration associations at the basis of the mass exodus from Germany to the United States in the 19th and 20th centuries.